2021
DOI: 10.1038/s41598-021-96933-0
|View full text |Cite
|
Sign up to set email alerts
|

Testing covariance models for MEG source reconstruction of hippocampal activity

Abstract: Beamforming is one of the most commonly used source reconstruction methods for magneto- and electroencephalography (M/EEG). One underlying assumption, however, is that distant sources are uncorrelated and here we tested whether this is an appropriate model for the human hippocampal data. We revised the Empirical Bayesian Beamfomer (EBB) to accommodate specific a-priori correlated source models. We showed in simulation that we could use model evidence (as approximated by Free Energy) to distinguish between diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…We have shown that conventional MEG analysis of eyes-open resting state data gives rise to an apparent high-frequency anterior temporal network which is reproducible across 100 Hz bands up until 400 Hz. These networks appear to be reproduciblenot only did we observe this in the Human Connectome Project resting state data, but similar topographies were also found in a 22-subject, task-based dataset collected in a previous study (Barry et al, 2019;O'Neill et al, 2021) that employed a different MEG system in a different country. Using the complimentary empty-room recordings of the HCP dataset we cannot simply replicate the network topographies without recording from the brain of a person within the MEG scanner (supplementary material).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have shown that conventional MEG analysis of eyes-open resting state data gives rise to an apparent high-frequency anterior temporal network which is reproducible across 100 Hz bands up until 400 Hz. These networks appear to be reproduciblenot only did we observe this in the Human Connectome Project resting state data, but similar topographies were also found in a 22-subject, task-based dataset collected in a previous study (Barry et al, 2019;O'Neill et al, 2021) that employed a different MEG system in a different country. Using the complimentary empty-room recordings of the HCP dataset we cannot simply replicate the network topographies without recording from the brain of a person within the MEG scanner (supplementary material).…”
Section: Discussionsupporting
confidence: 85%
“…We also analysed a second task-based dataset, which has been explored in previous studies (Barry et al, 2019; O’Neill et al, 2021). 22 native English speakers (14 female, aged 27±7 [mean±SD] years) participated in study that involved generating novel scene imagery.…”
Section: Methodsmentioning
confidence: 99%
“…There are several considerations when using beamformers with OPM data. First, traditional beamformers tend to fail in situations of highly correlated neuronal sources ( Van Veen et al., 1997 ), for example during binaural auditory stimulation ( Popov et al., 2018 ), or cognitive tasks involving bilateral hippocampi ( O'Neill et al., 2021 ). However, there are sparse source reconstruction techniques that are more robust to correlated sources such as “champagne” ( Cai et al., 2021 ; Owen et al., 2012 ), or “Multiple Sparse Priors” for correlated priors ( Friston et al., 2008 ; López et al., 2014).…”
Section: Signal Processing Strategies For Opmsmentioning
confidence: 99%
“…A subset of these same regions were involved in the theta/alpha changes found during 18 to 19s of overlap compared to non-overlap video-watching (Fig 2.B), including the Inferior parietal lobe, hippocampus, retrosplenial cortex, and precuneus. Although the effect appears to be isolated to the right hemisphere, we do not make inferences about the lateralisation because the beamformer algorithm can output illusory lateralised effects (O’Neill et al, 2021).…”
Section: Resultsmentioning
confidence: 99%